PELATIHAN APRESIASI SASTRA SEBAGAI SARANA MEMBENTUK MORAL ANAK-ANAK PASIR PUTIH BATAM - Dairi Sapta Rindu Simanjuntak; Yunisa Oktavia; Emil Eka Putra (ASOSIASI IDEBAHASA KEPRI, 2019)
Current technological advances have a huge effect on children's personality. This can be proven in various ways, one of which is the use of language. At present, the use of standard language is replaced by the words called alay or lebay language. Another thing that can be observed is the fading or loss of a sense of nationalism, and the spirit of struggle. A more worrying problem is the Internet Addiction Disorder—children cannot physically stop checking Facebook, playing online games excessively, and even worse, downloading and watching pornographic videos on YouTube. As a civilized and cultured nation, such situations are clearly very unfavorable for the future of the nation, especially its future generations, who are expected to be intellectually, emotionally, spiritually, and socially smart. In this context, serious efforts from all components of the nation to build a